Snake Venomics of Central American Pitvipers: Clues for Rationalizing the Distinct Envenomation Profiles of Atropoides nummifer and Atropoides picadoi - Angulo Ugalde, Yamileth (2008)
We report the proteomic characterization of the Central American pitvipers Atropoides nummifer and Atropoides picadoi. The crude venoms were fractionated by reverse-phase high-performance liquid chromatography (HPLC), followed by analysis of each chromatographic fraction by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), N-terminal sequencing, matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass fingerprinting, and collision-induced dissociation-tandem mass spectrometry (CID-MS/MS) of tryptic peptides. Each venom contained a number of bradykinin-potentiating peptides and around 25–27 proteins of molecular masses in the range of 7–112 kDa, belonging to only nine different toxin families (disintegrin, DC fragment, snake venom vascular endothelial growth factor, phospholipases A2, serine protease, cysteine-rich secretory proteins, C-type lectins, L-amino acid oxidase, and Zn2+-dependent metalloproteases), albeit distinctly distributed among the two Atropoides species. In addition, A. nummifer expresses low amounts of a three-finger toxin not detected in the venom of A. picadoi. The major toxins of A. nummifer belong to the PLA2 (relative abundance, 36.5%) and the serine proteinase (22%) families, whereas the most abundant A. picadoi toxins are Zn2+-dependent metalloproteinases (66.4%). We estimate that the similarity of venom proteins between the two Atropoides taxa may be around 14–16%. The high degree of differentiation in the venom proteome among congeneric taxa emphasizes unique aspects of venom composition of related species of Atropoides snakes and points to a strong role for adaptive diversification via natural selection as a cause of this distinctiveness. On the other hand, their distinct venom toxin compositions provide clues for rationalizing the low hemorrhagic, coagulant, and defibrinating activities and the high myotoxic and proteolytic effects evoked by A. nummifer snakebite in comparison to other crotaline snake venoms and the high hemorrhagic activity of A. picadoi.